Biodegradable Nanoparticles Mediated Co-delivery of Erlotinib (ELTN) and Fedratinib (FDTN) Toward the Treatment of ELTN-Resistant Non-small Cell Lung Cancer (NSCLC) via Suppression of the JAK2/STAT3 Signaling Pathway - Chen, Donglai; Zhang, Fuquan; Wang, Jinhui; He, Hua; Duan, Shanzhou; Zhu, Rongying; Chen, Chang; Yin, Lichen; Chen, Yongbing (Frontiers in Pharmacology, 2018)
Background Erlotinib (ELTN)-based targeted therapy as first-line treatment for EGFR-mutant lung cancers suffers from insufficient selectivity, side effects, and drug resistance, which poses critical challenges in the clinical setting. Acquired resistance of ELTN results in extremely poor prognoses of non-small cell lung cancer (NSCLC) patients, wherein activation of the JAK2/STAT3 signaling pathway has been proven to induce acquired ELTN resistance. Methods In this study, we developed a nanoparticle (NP) delivery system based on FDA-approved PEG-PLA for the co-delivery of ELTN and fedratinib (FDTN, a small-molecular, highly selective JAK2 inhibitor). Both ELTN and FDTN could be encapsulated into the PEG-PLA NPs via optimization of the encapsulation method. The effect of NPs on NSCLC cells was evaluated by MTT assay. Western blotting was performed to study the molecular mechanisms of NPs inhibiting the downstream pathways of EGFR in vitro. The histological analysis and protein expression in vivo were assessed by hematoxylin/eosin (H&E) staining and immunohistochemistry, respectively. Results The drug cargoes exhibited great stability, and could be released more efficiently in the acidic tumorous condition. Mechanistic study showed that FDTN notably down-regulated the expression levels of proteins in the JAK2/STAT3 signaling pathway, including p-EGFR, p-JAK2, p-STAT3 and Survivin, therefore reversing the ELTN resistance. As a result, synergistic anti-cancer effect was achieved by PEG-PLA NPs encapsulating both ELTN and FDTN in ELTN-resistant NSCLC tumors both in vitro and in vivo, and lower systemic side effect was noted for the co-delivery NPs compared to free drugs. Conclusion This study provides a promising approach to overcome the ELTN resistance in the treatment of NSCLC, and the use of FDA-approved materials with clinically applied/investigated chemical drugs may facilitate the translation of the current delivery system.